2019
DOI: 10.1111/mcn.12893
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding progression in late preterm infants from birth to one month

Abstract: This study aimed to describe and compare breastfeeding progression, infants' feeding behaviours, maternal feeding difficulties, and mothers' usage of breastfeeding interventions for singleton late preterm (LPT) and term infants. A further aim was to identify associated factors for exclusive breastfeeding at breast at 1 month in LPT infants.This was a cohort study where mothers of LPT infants from a neonatal unit (n = 60), LPT infants from a maternity unit (n = 62), and term infants from a maternity unit (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…According to previous studies, a higher percentage of first-time mothers, with some declared pathology during pregnancy and delivered by cesarean section, were found among PT groups [ 35 ]. In addition, as was expected due to the limitations widely described in initiation and maintenance of breastfeeding in PT [ 36 ], higher differences were detected in the prevalence of breastfeeding between the groups analysed. In contrast to the 42% of the FT newborns in the sample continuing to be breastfed up to 6 months of age, in compliance with WHO recommendations, less than 15% of PT maintained it [ 37 ].…”
Section: Discussionsupporting
confidence: 61%
“…According to previous studies, a higher percentage of first-time mothers, with some declared pathology during pregnancy and delivered by cesarean section, were found among PT groups [ 35 ]. In addition, as was expected due to the limitations widely described in initiation and maintenance of breastfeeding in PT [ 36 ], higher differences were detected in the prevalence of breastfeeding between the groups analysed. In contrast to the 42% of the FT newborns in the sample continuing to be breastfed up to 6 months of age, in compliance with WHO recommendations, less than 15% of PT maintained it [ 37 ].…”
Section: Discussionsupporting
confidence: 61%
“…Although LPT infants were breastfed exclusively to a lesser extent than term infants at 1 month, a more positive trend was seen in the following months. In a previous study, 4 we showed that LPT mothers reported an increase in exclusive breastfeeding during the first month after birth, which did not occur in term mothers. Hence, these studies taken together show that LPT mother‐infant dyads have the capacity and resources to transition from any to exclusive breastfeeding in the first 4 months.…”
Section: Discussionmentioning
confidence: 55%
“…14 In a previous study, we described the differences in breastfeeding during the first month in LPT infants in the NICU, LPT infants from the maternity unit and term infants. 4 The aim of this study was to describe, and compare, the experiences of mothers of LPT and term-born infants during the first year, with regard to breastfeeding duration, feeding, worries, depression and stress. A further aim was to identify factors associated with shorter breastfeeding duration of LPT infants.…”
mentioning
confidence: 99%
“…The exclusive BF rate and BF duration in hospitalised preterm infants are significantly lower than those in full-term newborns. [51][52][53][54] Preterm infants are transferred to the NICU immediately after birth for disease observation, diagnosis and treatment, which results in separation of mother and child, leading to insufficient lactation, an important factor that affects BF in preterm infants. 55 BF impacts the health economics of developing countries, improves the health of mothers and infants and reduces social inequities while reducing the incidence of infectious diseases, especially for disadvantaged children in poor areas.…”
Section: Discussionmentioning
confidence: 99%